Triazolyl phenyl disulfides: 8-Amino-7-oxononanoate synthase inhibitors as potential herbicides - Hahn, Hoh-Gyu; Choi, Jung-Sup; Lim, Hee Kyung; Lee, Kee-In; Hwang, In Taek (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2015)
The chemical validation of a potential herbicide target was investigated with 8-amino-7-oxononanoate synthase (AONS, also known as 7-keto-8-aminopelargonate synthase, KAPAS) and triazolyl phenyl disulfide derivatives in vitro and in vivo. AONS activity was completely inhibited by these synthesized compounds, with an IC50 of 48 to 592 mu M in vitro. Forty five-day old Arabido psis thaliana plants were completely killed by representative compound KHG23844 {N-(2-fluorophenyl)-3-(phenyldisulphanyl)-1H-1,2,4-triazole-1-carboxamide} at the application rate of 250 g ha(-1) of foliar treatment in greenhouse conditions. Foliar application of 1000 g ha(-1) KHG23844 induced 2.3-fold higher L-alanine accumulation in the treated A. thaliana plants. Foliar supplement of 1 mM biotin at 1 and 2 days before KHG23844 application effectively recovered the growth inhibition of A. thaliana plant treated with KHG23844. The results strongly suggested that representative compound KHG23844 and its derivatives are potential AONS inhibitors. (C) 2015 Elsevier Inc. All rights reserved.
Keywords: PROTOPORPHYRINOGEN OXIDASE; PLANTS; TARGET; BIOSYNTHESIS; CHLOROPHYLL; MECHANISM; ACID